Medical activity as a subject of criminal law regulation - Siubayeva, N.Zh.; Kabzhanov, A.T. (Bulletin of the Karaganda University “Law Series”, 2019)
The aim of the study is to determine the general mechanisms of legal and separate criminal and legal regulation of medical activities. The article is devoted to the legal regulation of relations in the sphere of medical services. In the article, the authors define the main problem of regulation of relations in the field of health care and suggest ways to solve it. The methodical bases of the article are general scientific methods, methods of theoretical analysis, empirical research. The authors, having considered the theoretical meaning of the concept of «medical care», analyzed the types of offences in the medical field in accordance with the legislation of the Republic of Kazakhstan. Along with the legislation regulating medical activities, much attention is paid to the issues of liability for violation of the procedure for the provision of medical services. An important role is played by the optimization of the health management system, which includes the assessment of the quality and effectiveness of medical services, the legal regulation of the relevant activities.The article pays special attention to the legal norms of the national legislation aimed at the regulation of medical activities, the normative legal acts with the division into groups, because of which the defects and contradictions in the legal regulation of relations to protect the rights of patients are revealed. The scientific novelty of the study is to conduct a comprehensive legal analysis of the legal regulation of medical activities in the Republic of Kazakhstan, to develop proposals for improving the legislation that protects the rights of patients.